Women Faculty Distressed: Descriptions and Consequences of Academic Contrapower Harassment - Lampman, C. (J Women High Educ, 2016)
Academic contrapower harassment (ACPH) occurs when someone with seemingly less power in an educational setting (e.g., a student) harasses someone more powerful (e.g., a professor). A representative sample of 289 professors from U.S. institutions of higher education described their worst incident with ACPH. Open-ended responses were coded using a keyword text analysis. Compared to the experiences of men faculty, women faculty reported that students were more likely to challenge their authority, argue or refuse to follow course policies, and exhibit disrespectful or disruptive behaviors. Although sexual harassment was uncommon, men faculty were more likely than women faculty to recount such incidents. Women faculty reported significantly more negative outcomes as a result of ACPH (e.g., anxiety, stress-related illness, difficulty concentrating, wanting to quit) than men faculty, and negative outcomes were most likely to result from ACPH involving intimidation, threats, or bullying from students. Implications for the prevention and reporting of ACPH are discussed.